2018
DOI: 10.1080/10245332.2018.1456023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of parenteral and oral treatment for nutritional vitamin B12 deficiency in children

Abstract: In this study, both oral and parenteral formulations were shown to be effective in normalizing vitamin B12 levels. We suggest that oral formulations may be considered to be safe as a first line treatment for vitamin B12 deficiency in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(69 reference statements)
0
7
0
2
Order By: Relevance
“…The dose range is remarkably wide and the initial usage doses proposed in children vary across the studies in the literature. Sezer et al 24 demonstrated the effectiveness of the oral dose in their study, in which the treatment of 10 out of 142 children started at a dose of 100 mcg/day and no side effect was observed. Yılmaz et al 26 indicated that they converted their treatments to hydroxocobalamin as a result of the oral cyanocobalamin treatment which was initiated at a dose of 250 mcg with 24 infants aged 2-18 months.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The dose range is remarkably wide and the initial usage doses proposed in children vary across the studies in the literature. Sezer et al 24 demonstrated the effectiveness of the oral dose in their study, in which the treatment of 10 out of 142 children started at a dose of 100 mcg/day and no side effect was observed. Yılmaz et al 26 indicated that they converted their treatments to hydroxocobalamin as a result of the oral cyanocobalamin treatment which was initiated at a dose of 250 mcg with 24 infants aged 2-18 months.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25] Bahadir et al 25 noted that the vitamin B12 levels did not decrease in children aged less than two years during the long term after treatment. On the other hand, Sezer et al 23,24 found that the intramuscular and oral administration of cyanocobalamin had a similar effect, and this finding has been reported in several book chapters as well. In our clinic, vitamin B12 replacement therapy is routinely administered peroral due to the effectiveness and practicality of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In children from 6 months of age, the effectiveness of oral vitamin substitution has recently been documented for nutritional deficiencies. Oral treatment could, therefore, be offered as a first-line treatment, with adequate compliance [ 19 ]. It presents various advantages, including being more suitable for a pediatric population with a lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Van de 260 gevonden onderzoeken waren er 20 gepubliceerd sinds de uitgebreide zoekstrategie van Wang et al Hiervan sloten er 18 niet aan bij onze vraagstelling en was er 1 niet-gerandomiseerd onderzoek bij kinderen. 5 Een RCT van Schijns et al uit 2018 bij volwassenen was wel geschikt voor nadere analyse. 6…”
Section: Zoekstrategieunclassified